Nephropathogenic Infectious Bronchitis Virus Mediates Kidney Injury in Chickens via the TLR7/NF-κB Signaling Axis - Li, Ning; Huang, Cheng; Chen, Wei; Li, Zhengqing; Hu, Guoliang; Li, Guyue; Liu, Ping; Hu, Ruiming; Zhuang, Yu; Luo, Junrong; Gao, Xiaona; Guo, Xiaoquan (Frontiers in Cellular and Infection Microbiology, 2022)
Nephropathogenic infectious bronchitis virus (NIBV) is one of the most important viral pathogens in the world poultry industry. Here, we used RT–qPCR, WB and immunofluorescence to explore the interaction between NIBV and the host innate immune system of the kidney. Multiple virions were found in the kidney tissues of the disease group under electron microscopy, and pathological changes such as structural damage of renal tubules and bleeding were observed by HE staining. In addition, we found that the mRNA levels of TLR7, TRAF6, and IKKβ were upregulated after NIBV infection. IRF7 mRNA levels decreased significantly at 5 dpi and increased significantly at 11 to 18 dpi. The NF-κB P65 mRNA level increased significantly at 5 to 18 dpi and decreased at 28 dpi. However, NIBV infection-induced NF-κB P65 protein levels were downregulated at multiple time points. Moreover, we demonstrated that the cytokine (IFN-γ, IL-8, and IL-6) mRNA and protein expression levels were increased significantly at multiple time points after NIBV infection. Furthermore, immunofluorescence analysis showed that NF-κB P65 and IFN-γ were mainly located in the nuclear or perinuclear region. The positive signal intensity of NF-κB P65 was significantly lower than that of the normal group at 1 to 5 dpi, and there was no significant change in the subsequent time period. The positive signal intensity of IFN-γ decreased significantly at 5 dpi, and increased significantly at 11 to 28 dpi. In conclusion, we found that NIBV promoted cytokine release through the TLR7/NF-κB signaling axis, thus causing kidney injury.